The effects of topical agents of fluticasone propionate, oxymetazoline, and 3% and 0.9% sodium chloride solutions on mucociliary clearance in the therapy of acute bacterial rhinosinusitis in vivo - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Objectives: The aims of the study were to determine: 1) how mucociliary activity in acute bacterial rhinosinusitis is affected; 2) how this activity is changed by therapy; 3) the effects of topical agents on mucociliary clearance, and 4) the most appropriate topical agent(s) to be used in the therapy of sinusitis. Study Design: Five groups of patients with acute bacterial rhinosinusitis were studied prospectively. Methods: All patients had 500 mg oral amoxicillin and 125 mg oral clavulanic acid preparations given three times daily for 3 weeks. According to the topical agent applications, these groups included: group I (n = 12), no topical treatment was given; group H (n = 14), two puffs for each nostril once daily of 50 mug/100 mL fluticasone propionate was given; group III (n = 9), one puff for each nostril three times daily of 0.05% oxymetazoline was given; group IV (n = 12), 3% sodium chloride (NaCl) (buffered to pH 6.5-7 at room temperature) was given; and group V (n = 13), 10-mL, solutions of 0.9% NaCl (buffered to pH 6.5-7 at room temperature) were given for nasal irrigations three times daily. All patients had medication for 3 weeks and were controlled each week. The saccharin method was used to measure nasal mucociliary clearance. To investigate the early effects of the topical agents for groups H to V, an additional test was repeated 20 minutes after the basal mucociliary clearance recordings. The test was repeated in the first, second, and third weeks of the treatment. Results: The mucociliary clearance was significantly slower in the acute bacterial rhinosinusitis group than in the control group. There was no significant difference between the basal mucociliary clearance and the 20th minute mucociliary clearance of the fluticasone propionate and 0.9% NaCl solution groups. The mean values of the basal and the 20 minute's mucociliary clearance of the oxymetazoline group were 24.72 +/- 6.16 and 15.5 +/- 7.45 minutes, respectively, which were statistically significant. The mean values of the basal and the 20th minute mucociliary clearance of the 3% NaCl solution groups were 19.45 +/- 9.35 and 15.45 +/- 8.20 minutes, respectively, which were also statistically significant. In the first group (without topical treatment), the basal mucociliary clearance became significantly shorter after the second week of treatment. In the first and second weeks of the treatment of the oxymetazoline group, the mucociliary clearance did not change significantly, but after the third week the mucociliary clearance was significantly shorter. In the 3%, NaCl solution group, significant improvement began from the first week and continued through the third week. Comparing the basal and the third weeks' mucociliary clearance values among the groups, the oxymetazoline and 3% NaCl solution groups revealed more significant improvement than the other groups, but this improvement was not different from the improvement of group I. There was still a statistically significant difference in the mucociliary clearance of the post-treatment sinusitis groups from the control group. Conclusions: The oxymetazoline and 3% NaCl solution groups seemed to be more effective in mucociliary clearance, but there was no significant difference in improvement among the groups. The improvement of acute bacterial rhinosinusitis takes more than 3 weeks, according to the mucociliary clearance values of the groups.
Keywords: acute bacterial rhinosinusitis; mucociliary clearance; treatment; oxymetazoline; fluticasone propionate; sodium chloride; FUROATE NASAL SPRAY; CILIARY BEAT; IN-VITRO; MUCOSA; SINUSITIS; SALINE; BETAMETHASONE; FREQUENCY; RABBIT; DROPS